Melanin-Concentrating Hormone acts through hypothalamic kappa opioid system and p70S6K to stimulate acute food intake. (1st March 2018) - Romero-Picó, Amparo; Sanchez-Rebordelo, Estrella; Imbernon, Monica; González-Touceda, David; Folgueira, Cintia; Senra, Ana; Fernø, Johan; Blouet, Clémence; Cabrera, Roberto; van Gestel, Margriet; Adan, Roger A.; López, Miguel; et al.
Abstract: Melanin-Concentrating Hormone (MCH) is one of the most relevant orexigenic factors specifically located in the lateral hypothalamic area (LHA), with its physiological relevance demonstrated in studies using several genetically manipulated mice models. However, the central mechanisms controlling MCH-induced hyperphagia remain largely uncharacterized. Here, we show that central injection of MCH in mice deficient for kappa opoid receptor ( k -OR) failed to stimulate feeding. To determine the hypothalamic area responsible for this MCH/ k -OR interaction, we performed virogenetic studies and found that downregulation of k -OR by adeno-associated viruses (shOprk1-AAV) in LHA, but not in other hypothalamic nuclei, was sufficient to block MCH-induced food intake. Next, we sought to investigate the molecular signaling pathway within the LHA that mediates acute central MCH stimulation of food intake. We found that MCH activates k -OR and that increased levels of phosphorylated extracellular signal regulated kinase (ERK) are associated with downregulation of phospho-S6 Ribosomal Protein. This effect was prevented when a pharmacological inhibitor of k -OR was co-administered with MCH. Finally, the specific activation of the direct upstream regulator of S6 (p70S6K) in the LHA attenuated MCH-stimulated food consumption. Our results reveal that lateral hypothalamic k -OR system modulates the orexigenic action of MCH via the p70S6K/S6 pathway. Highlights: Central MCH fails to stimulate food intake in k -OR-deficient mice. k -OR, in the lateral hypothalamic area (LHA), modulates acute MCH-induced feeding. Central MCH activates k -OR in the LHA, and reduces phosphorylated levels of S6 ribosomal protein. The genetic activation of p70S6K in the LHA reduces MCH-induced feeding.